1 H detection and dynamic nuclear polarization–enhanced NMR of Aβ 1-42 fibrils - Bahri, Salima; Silvers, Robert; Michael, Brian; Jaudzems, Kristaps; Lalli, Daniela; Casano, Gilles; Ouari, Olivier; Lesage, Anne; Pintacuda, Guido; Linse, Sara; Griffin, Robert G. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Amyloid-β (Aβ) is the subject of intense scrutiny because of its close association with Alzheimer’s disease (AD), which currently afflicts about 50 million people worldwide. The results reported in this manuscript focus on the new possibilities provided by ultrafast magic-angle spinning (MAS) 1 H detection and fast-MAS dynamic nuclear polarization (DNP), which have ushered in a new era for NMR-based structural biology, but whose potential has not yet been fully exploited for the structural investigation of complex amyloid assemblies. This work demonstrates the expeditious structural analysis of amyloid fibrils, without requiring preparation of large sample amounts, and sets the stage for future studies of unlabeled AD peptides derived from tissue samples available in limited quantities. Several publications describing high-resolution structures of amyloid-β (Aβ) and other fibrils have demonstrated that magic-angle spinning (MAS) NMR spectroscopy is an ideal tool for studying amyloids at atomic resolution. Nonetheless, MAS NMR suffers from low sensitivity, requiring relatively large amounts of samples and extensive signal acquisition periods, which in turn limits the questions that can be addressed by atomic-level spectroscopic studies. Here, we show that these drawbacks are removed by utilizing two relatively recent additions to the repertoire of MAS NMR experiments—namely, 1 H detection and dynamic nuclear polarization (DNP). We show resolved and sensitive two-dimensional (2D) and three-dimensional (3D) correlations obtained on 13 C, 15 N-enriched, and fully protonated samples of M 0 Aβ 1-42 fibrils by high-field 1 H-detected NMR at 23.4 T and 18.8 T, and 13 C-detected DNP MAS NMR at 18.8 T. These spectra enable nearly complete resonance assignment of the core of M 0 Aβ 1-42 (K16-A42) using submilligram sample quantities, as well as the detection of numerous unambiguous internuclear proximities defining both the structure of the core and the arrangement of the different monomers. An estimate of the sensitivity of the two approaches indicates that the DNP experiments are currently ∼6.5 times more sensitive than 1 H detection. These results suggest that 1 H detection and DNP may be the spectroscopic approaches of choice for future studies of Aβ and other amyloid systems.